CONNECT a personal remote messaging and monitoring system to aid people with disabilities. - Zaruba, Gergely (IEEE Communications magazine)
In this article we introduce CONNECT, an infrastructure running on small wireless devices (e.g., PDA phones) and servers that aids people with disabilities in leading their everyday lives. We refer to the target (client) devices as personal portable devices (PPDs). The architecture of the CONNECT system is described, with emphasis on the accessibility services provided to its clients. As an example, the reminder service of CONNECT is profiled where care providers and community organizers (or general users who have appropriate rights) can send timely reminders to the PPD owners, giving them a chance to respond to these messages. In conjunction with the connect project, 600 PPDs are deployed to people with disabilities for evaluation purposes.